A practical technique for connecting PV generator to single-phase grid. (August 2015) - Marrekchi, Amal; Kammoun, Soulaymen; Sallem, Souhir; Kammoun, Mohamed Ben Ali
Highlights: Grid connected PV system was developed and simulated. Two diode model of PV panel was presented, simulated and validated. New, easy and efficient methods for MPPT and for coupling. Steps of coupling the PVG to the grid and injection of the PVG power into it are explained. Abstract: Nowadays, photovoltaic energy is becoming an increasingly important renewable energy in the world. A grid connected photovoltaic system consists of extracting the maximum power from the PV panel. This paper presented a PV-grid connected system and proposed a practical and efficient method for coupling a photovoltaic generator (PVG) on a single-phase electric grid throughout two conversion stages namely DC–DC boost converter and voltage source inverter (VSI). The DC–DC converter ensures that a maximum power extraction from the PVG and that the VSI matches the grid requirement for the energy produced. In fact, before discussing the injection of the produced power by the PVG into the electric grid, connection requirement have to be met. We presented then the coupling conditions to respect and the way to deal with them. The proposed method has been simulated revealing the ability of our system to highlight the coupling instance. The obtained results show the transient analysis of coupling and the efficiency of the proposed technique.